Pelayanan Administrasi Publik Pada Kantor Desa Sakita Kecamatan Bungku Tengah Kabupaten Morowali - Asniati; Halim, Rahmawati; Rapi, Muh. (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
The purpose of this research is to analyze public administration services at the Sakita Village Office, Bungku Tengah Sub-district, Morowali Regency. This study was conducted using a qualitative descriptive method with a descriptive research type. The data used consisted of primary and secondary data. Data collection techniques included observation, interviews, and documentation, with 5 informants. Data analysis followed Miles, Huberman, and Saldana’s model: data collection, data condensation, data display, and conclusion drawing.This study employed Lovelock’s theory of five public service indicators: Tangible, Reliability, Responsiveness, Assurance, and Empathy. The results show that public administration services in Sakita Village are fairly good, demonstrating progress in digitalization, transparency, and officers’ attentiveness, particularly through the implementation of the Peapua application. However, its implementation is not yet optimal due to limited socialization, inadequate facilities, and low discipline among village officials who are often absent. These issues cause delays in services, such as the issuance of domicile certificates, which often exceed the standard processing time stated in the SOP. Among the five service dimensions, Tangible and Reliability remain constrained by infrastructure, staff presence, and technical issues; Responsiveness and Empathy are rated positively as officers are proactive, friendly, and communicative; while Assurance is adequate but weakened by dependence on a single operator. Therefore, improvements in discipline, staff capacity, equitable distribution of responsibilities, and the provision of facilities and infrastructure are urgent to ensure more effective and efficient public services.